2011
DOI: 10.4081/ejh.2011.e6
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that muscle cells do not express the histidine-rich glycoprotein associated with AMP deaminase but can internalise the plasma protein

Abstract: Histidine-rich glycoprotein (HRG) is synthesized by liver and is present at relatively high concentration in the plasma of vertebrates. We have previously described the association of a HRG-like molecule to purified rabbit skeletal muscle AMP deaminase (AMPD). We also provided the first evidence for the presence of a HRG-like protein in human skeletal muscle where a positive correlation between HRG content and total determined AMPD activity has been shown. In the present paper we investigate the origin of skel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 33 publications
2
12
0
Order By: Relevance
“…Moreover, in a study on the origin of skeletal muscle HRG, we have demonstrated that muscle cells do not synthesize the protein but instead can actively internalize it from plasma, indicating for the first time that HRG can be carried to tissues via circulation (Sabbatini et al 2011). We have also described a positive correlation in human skeletal muscle between the content of HRG and the level of AMPD1 activity that it is known to be predominant in type IIB fast-twitch glycolytic fibers (Sabbatini et al 1999(Sabbatini et al , 2006.…”
Section: Introductionmentioning
confidence: 85%
“…Moreover, in a study on the origin of skeletal muscle HRG, we have demonstrated that muscle cells do not synthesize the protein but instead can actively internalize it from plasma, indicating for the first time that HRG can be carried to tissues via circulation (Sabbatini et al 2011). We have also described a positive correlation in human skeletal muscle between the content of HRG and the level of AMPD1 activity that it is known to be predominant in type IIB fast-twitch glycolytic fibers (Sabbatini et al 1999(Sabbatini et al , 2006.…”
Section: Introductionmentioning
confidence: 85%
“…The N-terminal sequence analysis of several tryptic peptides of this protein revealed a striking similarity to the fragments from rabbit plasma HRG. Further investigation, however, indicated that skeletal muscle cells do not synthesize the muscle variant of HRG but can instead actively internalize it from plasma (Sabbatini et al, 2011). Further investigation, however, indicated that skeletal muscle cells do not synthesize the muscle variant of HRG but can instead actively internalize it from plasma (Sabbatini et al, 2011).…”
Section: Localization and Biosynthesismentioning
confidence: 93%
“…The role of HPRG as zinc chaperone 3.1. HPRG participates as zinc metallochaperone in the assembly and maintenance of skeletal muscle AMP deaminase According to Sabbatini et al [4], skeletal muscle cells do not transcribe HPRG but internalize the protein from serum. The percentage of internalized HPRG was reduced in the presence of heparin, indicating that heparin may compete with the cell surface GAGs in binding HPRG.…”
Section: The Histidine-proline-rich Central Region Of Hprg: Potentialmentioning
confidence: 99%
“…A protein very similar in sequence to HPRG co-purified with rabbit skeletal muscle AMP deaminase (AMPD) preparation [3]. It has been later demonstrated that the HPRG present in rabbit skeletal muscle is acquired from plasma since skeletal muscle cells do not synthesize the protein [4].…”
Section: Introductionmentioning
confidence: 99%